TRANSFORMER HEALTH CONDITION ANALYSIS BASED ON HEALTH INDEX AND FAILURE METHOD - Iswadi Hasyim Rosma; Boy Ihsan; Jikro Pikri (TESLA: Jurnal Teknik Elektro, 2025)
Transformers are one of the important assets whose health conditions need to be monitored to maintain operating reliability and prevent failures. Regular monitoring and testing can be done on transformer oil and insulating paper (furan). This article aims to evaluate the health index, estimate the remaining life and detect potential transformer failures. The test data used was obtained from two transformers at a biodiesel producing company in Indonesia, such as Dissolved Gas Analysis, Breakdown Voltage, Water Content, Acid, Interfacial Tension and 2 Fal (furan) tests. The method used in the diagnosis of transformer health conditions is the transformer health index method and analysis of potential failures based on the evaluation of Total Dissolved Combustible Gas, Roger's Ratio and Duval's Triangle. The results show that both transformers are in a healthy condition with a health index of 72% and 89%, which fall into the “Good” and “Very Good” categories, and the estimated operational life is more than 10 years and 15 years, respectively. However, the failure analysis results indicated an overheating failure with a temperature exceeding 700 ºC. Although the overall transformer condition is still good, preventive maintenance measures are still recommended to avoid more serious damage in the future Abstrak Transformator merupakan salah satu aset penting yang kondisi kesehatannya perlu dipantau untuk menjaga keandalan operasi dan mencegah kegagalan. Pemantauan dan pengujian secara berkala dapat dilakukan terhadap minyak transfomator dan isolasi kertas (furan). Artikel ini bertujuan untuk mengevaluasi indeks kesehatan, estimasi sisa umur dan mendeteksi potensi kegagalan transformator. Data pengujian yang digunakan diperoleh dari dua transformator di sebuah perusahaan penghasil biodiesel di Indonesia yaitu data hasil pengujian Dissolved Gas Analysis, Breakdown Voltage, Water Content, Acid, Interfacial Tension serta 2 Fal (furan). Metode yang digunakan dalam diagnosis kondisi kesehatan transformator adalah metode indeks kesehatan transformator serta analisis potensi kegagalan berdasarkan evaluasi Total Dissolved Combustible Gas, Roger’s Ratio dan Duval’s Triangle. Hasil penelitian menunjukkan bahwa kedua transformator berada dalam kondisi sehat dengan indeks kesehatan 72% dan 89%, yang termasuk kategori “Baik” dan “Sangat Baik”, serta estimasi umur operasional masing-masing lebih dari 10 tahun dan 15 tahun. Namun demikian, hasil analisis kegagalan mengindikasikan adanya kegagalan overheating dengan suhu melebihi 700 ºC. Meskipun kondisi keseluruhan transformator masih baik, tindakan pemeliharaan preventif tetap direkomendasikan untuk menghindari kerusakan yang lebih serius dimasa mendatang.